PEMBERDAYAAN KELOMPOK NELAYAN 64 BAHARI KECAMATAN BULAK KOTA SURABAYA MELALUI INOVASI TEKNOLOGI DAN EDUKASI KELAUTAN TERPADU: EMPOWERMENT OF THE 64 BAHARI FISHERMEN'S GROUP IN THE BULAK DISTRICT OF SURABAYA CITY THROUGH TECHNOLOGICAL INNOVATION AND INTEGRATED MARINE EDUCATION - Widodo, A. Basuki; Azhar, Ali; Azhar, Suryadhi; Sofijanto, M. Arief; Rosana, Nurul; Sugianto, Erik; Agustin, Titiek Indhira; Prayogi, Urip; Mu’ninim, Amirul Mu’ninim; Aditya, Bagus Kusuma (Universitas Hang Tuah Surabaya, 2025)
The Bahari 64 fishermen group located in Bulak District, Surabaya City is one of the fishermen groups fostered by the Faculty of Engineering and Marine Sciences, Hang Tuah University. As a form of concern for the community in introducing current developments in renewable technology and a form of the Faculty of Engineering and Marine Sciences' commitment to Community Service, it is necessary to conduct socialization and technological counseling to fishermen, in this case the 64 Bahari fishermen group. Android-based technology, modern materials and knowledge related to ship stability and ship repair technology are some of the information conveyed through the Focus Group Discussion between the 64 Bahari Fishermen Group and the Faculty of Engineering and Marine Sciences. The activities carried out are expected to have a positive impact and be directly beneficial to the community, especially those who work as fishermen